2023
DOI: 10.1093/mnras/stad1340
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear activity in z < 0.3 QSO 2’s mainly triggered by galaxy mergers

Abstract: We investigate the role of the close environment on the nuclear activity of a sample of 436 nearby (z < 0.3) QSO 2’s – selected from SDSS-III spectra, via comparison of their environment and interaction parameters with those of a control sample of 1308 galaxies. We have used the corresponding SDSS images to obtain the number of neighbour galaxies N, tidal strength parameter Q and asymmetry parameters. We find a small excess of N in the QSOs compared to its three controls, and no difference in Q. The mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…However, the relative roles and importances of these two mechanisms for driving SMBH growth remain unclear. Observational studies disagree on fundamental questions such as whether AGNs are more often found in galaxy mergers (e.g., Canalizo & Stockton 2001;Villar-Martín et al 2011;Ellison et al 2019;Araujo et al 2023;Pierce et al 2023) or not (e.g., Dunlop et al 2003;Gabor et al 2009;Cisternas et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, the relative roles and importances of these two mechanisms for driving SMBH growth remain unclear. Observational studies disagree on fundamental questions such as whether AGNs are more often found in galaxy mergers (e.g., Canalizo & Stockton 2001;Villar-Martín et al 2011;Ellison et al 2019;Araujo et al 2023;Pierce et al 2023) or not (e.g., Dunlop et al 2003;Gabor et al 2009;Cisternas et al 2011).…”
Section: Introductionmentioning
confidence: 99%